The law between justice and godliness: on the infidelity and banishment of aristocrats and nobles in the Hispanic-Visigoth kingdom of Toledo (636-654) - Frighetto, Renan (Romanitas - Revista de Estudos Grecolatinos, 2019)
In the Hispanic-Visigoth kingdom of Toledo (VI-VII centuries), the elaboration of the Law started from the royal authority. The Liber Iudiciorum/Lex Visigothorum, a legal compilation associated with the late Roman tradition and published in an organized manner from 654 onwards, presents a variety of legal norms promulgated by the royal power that also involved the problems linked to the breaking of the oath of fidelity between the aristocratic segments and the king. The aristocratic infidelity created serious problems for the king, especially those who fled abroad and attacked the bordering areas of the kingdom. These fugitives, framed in the profile of the outcast, appear in the secular and ecclesiastical legal documentation more broadly and are the object of our analysis in this study.